Case Report: ALK-positive histiocytosis presenting as an adrenal mass: a diagnostic trap due to unusual morphology - Ma, Wenjing; Zhou, Shenda; Lu, Jiali; Wei, Haiming; Huang, Yongta (Frontiers in Oncology, 2026)
BackgroundThe differential diagnosis of an adrenal mass is critical for clinical management. We report a case that expanded the spectrum of a rare disease and present a novel diagnostic trap for both pathologists and clinicians.MethodsHistopathological, immunohistochemical (CD68, CD163, ALK), and molecular (FISH) analyses were performed on a right adrenal tumor from an 81-year-old male.ResultsThe tumor was diagnosed as ALK-positive histiocytosis. Uniquely, it presented as a primary adrenal mass with unusual morphology. The tumor cells showed marked anaplasia and emperipolesis. Apart from classic xanthogranuloma areas, the tumor exhibited hypercellular and hypocellular zones. Neoplastic cells in the hypercellular regions displayed anaplastic features, including a high nuclear-to-cytoplasmic ratio, prominent nucleoli, and observable mitotic figures. In contrast, neoplastic cells in the hypocellular areas were cytologically bland within a myxoid stroma. Neoplastic cells were positive for macrophage markers CD68, CD163 and ALK. Fluorescence in situ hybridization (FISH) demonstrated ALK gene rearrangements. The patient was disease-free after 8 months.ConclusionTo our knowledge, this is the first documentation of primary ALK-positive histiocytosis in the adrenal gland. The presence of anaplastic features poses a high risk of misdiagnosis as a sarcoma or carcinoma, potentially leading to overly aggressive therapy. Therefore, we advocate for the inclusion of this entity in the differential diagnosis of adrenal neoplasms and recommend routine ALK testing in similar challenging cases to guide precise management and avoid therapeutic errors.